Guide Swap enables genome-scale pooled CRISPR–Cas9 screening in human primary cells. (November 2018) - Ting, Pamela; Parker, Albert; Lee, J.; Trussell, Chris; Sharif, Orzala; Luna, Fabio; Federe, Glenn; Barnes, S.; Walker, John; Vance, Julie; Gao, Mu-Yun; Klock, Heath; et al.
Abstract CRISPR–Cas9 screening allows genome-wide interrogation of gene function. Currently, to achieve the high and uniform Cas9 expression desirable for screening, one needs to engineer stable and clonal Cas9-expressing cells—an approach that is not applicable in human primary cells. Guide Swap permits genome-scale pooled CRISPR–Cas9 screening in human primary cells by exploiting the unexpected finding that editing by lentivirally delivered, targeted guide RNAs (gRNAs) occurs efficiently when Cas9 is introduced in complex with nontargeting gRNA. We validated Guide Swap in depletion and enrichment screens in CD4+ T cells. Next, we implemented Guide Swap in a model of ex vivo hematopoiesis, and identified known and previously unknown regulators of CD34+ hematopoietic stem and progenitor cell (HSPC) expansion. We anticipate that this platform will be broadly applicable to other challenging cell types, and thus will enable discovery in previously inaccessible but biologically relevant human primary cell systems. Guide Swap challenges the hypothesis that Cas9–sgRNA binding is irreversible. The authors find that instead, nontargeting sgRNAs are swapped for targeting sgRNAs in the Cas9 complex. The method allows genome-scale functional screens in primary cells